Exploring the Cognitive and Social Benefits of Bubble Blowing Activities in Early Childhood Development: A Thought Experiment Approach - Adeoye, Moses Adeleke; Sulaimon, Jamiu Temitope; Peters, Olorunjeedalo Anu (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2025)
Play is universally recognised as a vital aspect of early childhood development, yet specific activities, such as bubble blowing, remain underexplored in the literature. This research investigates bubble-blowing's cognitive, social, and emotional impacts on young children, providing empirical evidence to support integrating such activities into early childhood curricula. Utilising a thought-experimental approach, the study engaged educators and parents in reflective discussions about children's experiences and observations during bubble-blowing activities. The findings reveal that bubble blowing significantly enhances cognitive skills, including problem-solving and critical thinking, as children explore scientific concepts through hands-on experimentation. Socially, the activity fosters collaboration, communication, and conflict resolution, demonstrating that structured and unstructured play can yield substantial social benefits. Emotionally, children express various feelings, from joy to frustration, contributing to their emotional regulation and resilience. In conclusion, bubble blowing is an effective tool for promoting holistic development in early childhood. This research contributes to the existing body of literature by providing specific insights into the developmental benefits of targeted play activity, emphasising the need for educators and parents to prioritise play-based learning. By highlighting the multifaceted advantages of bubble-blowing, the study advocates for its inclusion in educational settings, ultimately enhancing the quality of early childhood education and fostering well-rounded development in young children.